THE INFLUENCE OF TOURISM ATTRACTION, ENTRY TICKET PRICES, AND WORD OF MOUTH ON THE DECISION TO VISIT TIRTA WAHYU ARTA TOURISM ATTENTION IN PEKALONGAN DISTRICT - Nazifa, Dina (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of tourist tricks, entrance ticket prices, and word of mouth on the decision to visit Tirta Wahyu Arta Tourism. The type of research used in this research is Associative Quantitative. The data collected uses primary data, namely data collected or obtained directly in the field. In this study there were 97 respondents used as samples. The sampling method uses purpose sampling, namely determining samples based on criteria. The analytical tool used is multiple linear regression analysis. Based on the results of the analysis, it is stated that tourist attraction has a positive and significant effect on the decision to visit with a calculated t value of 5.188 and a significant value of 0.000. The entrance ticket price has a positive and significant effect on the decision to visit with a calculated t value of 3.954 and a significant value of 0.000. Word of Mouth has a positive and significant effect on Visiting Decisions with a calculated t value of 2.698 and a significant value of 0.008.